My friend is moving - Kohler, Christine, 1953-; Neely, Keith, 1943- (St. Louis : Concordia Pub. House, 1985)
Knowing they may not see each other again, Jennifer helps her friend feel better about moving by reminding her that we remain friends with Jesus even though we don't see Him.
Keywords: Childrens's stories, American; Moving, Household -- Fiction; Christian life -- Fiction; Friendship -- Fiction